EFEKTIVITAS PEMBELAJARAN DIFERENSIASI PADA PENERAPAN NILAI-NILAI PANCASILA DI KELAS VI SEKOLAH DASAR - Dewi, Atika; Rosyidah; Hidayati, Isnah; Santoso; Rondli, Wawan Shokib (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2025)
This study aims to describe the implementation of differentiated learning in the practice of Pancasila values in elementary school students. A descriptive qualitative research method was used, with data collection techniques including classroom observations, teacher interviews, and documentation of students' learning outcomes at three different elementary schools. The results showed that teachers consistently applied differentiated learning by adjusting the content, process, product, and learning environment according to the students' needs. This approach successfully enhanced students' active involvement, learning motivation, and character development in alignment with the values of Pancasila. Differentiated learning has characteristics that align with supporting learning theories, such as Piaget's cognitive development theory, Vygotsky's Zone of Proximal Development (ZPD) theory, Kohlberg's theory of moral development, and Bruner's constructivist theory, which indicate that differentiated learning can be applied in the development of cognitive, affective, psychomotor, and character aspects that reflect Pancasila values through Civics Education (PPKn). However, there are some challenges, such as the implementation of initial assessments, limited time, and learning resources that need attention. This study provides implications for the development of effective and enjoyable Civics Education strategies at the elementary school level.